Proceedings of the 18th LACCEI International Multi-Conference for Engineering, Education, and Technology: Engineering, Integrat 2020
DOI: 10.18687/laccei2020.1.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de Residuos Plásticos y Catalizadores para su Aplicación en Procesos Termoquímicos

Abstract: In Peru the plastics industry generates plastic waste of which only 50% are recycled. Likewise, fluidized catalytic cracking units annually produce significant amounts of catalyst that must be disposed as a solid residue. In this investigation, three samples of plastic waste from urban solid waste, a sample of fresh catalyst and another of FCC equilibrium catalyst were characterized, the equilibrium catalyst sample was heat treated to restore its catalytic properties and characterized with and without previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Additionally, the market of liquid fuels in Peru must comply with established quality parameters based on their physicochemical properties. Then, fuel samples must be characterized by standardized tests to determine their quality [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the market of liquid fuels in Peru must comply with established quality parameters based on their physicochemical properties. Then, fuel samples must be characterized by standardized tests to determine their quality [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Plastic waste is a promising source of liquid fuels [9]. Previous studies have reported the optimization and characterization of liquid fuels obtained from the pyrolysis of plastic waste [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%